2022
DOI: 10.36805/jtmmx.v3i2.2975
|View full text |Cite
|
Sign up to set email alerts
|

An Addition of Ethanol and Patchouli Oil on Pertamax: The Case Study of Their Effect on Exhaust Gas Emission for 4-stroke Engine

Abstract: Industrial sector has been focused on the transportation and automotive service due to their essential for many people in every daily life. Currently, almost everyone has a motorized vehicle which also has an effect on improving the country’s economy. On the other hand, this raises concerns about the occurrence of a global warming phenomenon. The more motorized vehicles were extremely impact on increasing the exhaust gasses that also have a negative impact to the environment, including carbon monoxide (CO) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This difference may be attributed to the inclusion of plant extracts and allantoin in the formulation. It is worth noting that the impact of additives on surface tension can vary; for instance, Farah et al reported a significant increase in surface tension with the addition of patchouli oil (5%) to a fuel mixture [27]. Conversely, the incorporation of allantoin (0.2%) in bioadhesive gels resulted in a decrease in surface tension of 4.05 to 7.03% [16].…”
Section: Evaluation Of Surface Tensionmentioning
confidence: 99%
“…This difference may be attributed to the inclusion of plant extracts and allantoin in the formulation. It is worth noting that the impact of additives on surface tension can vary; for instance, Farah et al reported a significant increase in surface tension with the addition of patchouli oil (5%) to a fuel mixture [27]. Conversely, the incorporation of allantoin (0.2%) in bioadhesive gels resulted in a decrease in surface tension of 4.05 to 7.03% [16].…”
Section: Evaluation Of Surface Tensionmentioning
confidence: 99%
“…For this step, it started with measuring the volume of the ball that used in this experiment. The volume is calculated using equation 2 [20]. Then, the important variable is the radius of the ball that is obtained from the measurement using vernier calipers.…”
Section: Sample Numbermentioning
confidence: 99%